A New Prognostic Index Combines the Metabolic Response and RECIST 1.1 to Evaluate the Therapeutic Response in Patients With Non-Small Cell Lung Cancer - Tang, Wenfang; Hou, Qingyi; Lin, Juntao; Li, Dongjiang; Lin, Jieshan; Chen, Jinghua; Qiu, Zhenbin; Chu, Xiangpeng; Yang, Xiongwen; Yan, Honghong; Wang, Shuxia; Wu, Yilong; et al. (Frontiers in Oncology, 2020)
ABSTRACT Aim: Response Evaluation Criteria in Solid Tumors (RECIST) is occasionally insufficient for evaluation. We proposed a new prognostic index (NPI) that combines the standardized uptake value (SUV), metabolic tumor volume (MTV) and RECIST. Methods: In total, 116 patients with lung cancer who underwent consecutive positron emission tomography-computed tomography prior to and after the initial treatment were included. We formulated the NPI by estimating the hazard ratios of overall survival for ∆MTV, ∆SUVmax and ∆D (tumor size based on RECIST). Progression-free survival (PFS) and overall survival (OS) were compared between RECIST and the NPI. Results: ROC curve analysis identified two cutoff values based on the NPI (≤-49.3% and ≥43.4%) to discriminate partial remission (NPR), stable disease (NSD) and progressive disease (NPD). Based on RECIST, survival analysis did not discriminate significantly on either PFS or OS between the PR, SD and PD groups. However, according to the NPI, PFS and OS differed significantly between the NPR, NSD, and NPD groups (training set: PFS, p = 0.048; OS, p = 0.026; validation set: PFS, p = 0.004; OS, p = 0.023). Moreover, therapeutic response based on NPI was independent prognostic factor for both PFS (NPR as reference, NSD: hazard ratio (HR) 2.04; 95% confidence interval (95% CI) 1.35-3.08; p = 0.001; NPD: HR 6.87; 95% CI 3.03-15.57; p < 0.001) and OS (NPR as reference, NSD: HR 1.64; 95% CI 1.05-2.57; p = 0.031; NPD: HR 3.56; 95% CI 1.59-7.95; p = 0.002). Conclusion: The NPI showed superiority for evaluation of the therapeutic response and survival for patients with non-small cell lung cancer, overcoming the limitations of RECIST.